Pengembangan Sistem Manajemen Toko Penjualan dan Servis Handphone berbasis Desktop (Studi Kasus: Toko FQ CELL Kota Batu) - Ananda Priatama; Tri Astoto Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
FQ Cell is a shop that serves phone sale and repair in Batu City which has been established since 2003. Business activities at FQ Cell generally consist of procurement, sales and financial reporting. In carrying out its business processes, FQ Cell is still experiencing several problems, namely the absence of records in the purchase process, stock recording and financial reporting. The absence of stock recording causes the process of finding items to take time. The next problem is the absence of financial report. This causes unknown data related to cash flow and operating profit and loss. A desktop-based shop management system was developed to solve these problems. The system was developed using the waterfall model with an object-oriented approach. The technology used in system development consists of C# as programming language and MySQL as database management. Unit testing, integration and validation have been carried out on the developed system and produce valid values. This system is expected to help shop owners in carrying out their business activities.